Body composition and muscle characteristics of division I track and field athletes - Hirsch, K. R.; Smith-Ryan, A. E.; Trexler, E. T.; Roelofs, E. J. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to evaluate event-specific body composition and muscle characteristics of track and field athletes and to assess body composition changes after 1 year. Sixty collegiate track and field athletes (mean ± SD; age = 19.2 ± 1.4 years, height = 174.6 ± 9.0 cm, and weight = 71.5 ± 12.5 kg) were stratified into 6 event groups. Total and regional body composition measurements were assessed using dual-energy x-ray absorptiometry. A panoramic scan of the vastus lateralis was taken with B-mode ultrasound to determine muscle cross-sectional area and echo intensity (EI). Body composition measurements were repeated a year later in a subset of returning athletes (n = 33). Throwers had significantly more absolute fat mass (FM; 21.6 ± 11.0 kg), total body mass (89.7 ± 17.4 kg), percent fat (23.6 ± 7.8), and trunk fat (9.4 ± 5.8 kg) than all other event groups (p = 0.05). Throwers had the most absolute lean mass (LM; 64.2 ± 11.7 kg; p > 0.05), but relative to body mass had relatively less LM (0.72 ± 0.08 kg; p = 0.05). Despite high FM, throwers had lower EI (63.4 ± 5.2 a.u). After 1 year, relative armLM increased slightly in all event groups (p = 0.05). Evaluation of muscle characteristics in addition to total and regional body composition may be valuable for improving performance, injury prevention, and assessing health risks. With appropriate training, track and field athletes may be able to minimize losses in LM and gains in FM between seasons.